Behavioral Antecedents of Green Skincare Purchases in the Zillennial Cohort: A Literature Review - Nugraha Kusbianto; Siti Yolanda Rahman Utami; Sri Wulan Sari Adi Pandur Hasesda; Lidya Veronica Christy Rihidima (CV. Ulil Albab Corp, 2025)
The green skincare market has emerged as a vital subject for academic inquiry and business innovation, driven by rising environmental concerns and a strong shift toward sustainable consumption. Focused on younger consumers, particularly Zillennials with heightened eco-consciousness, this review examines the factors that motivate purchasing behavior beyond mere green purchase intention (GPI). Although many studies have addressed GPI, little attention has been given to the direct antecedents of actual buying behavior. In particular, prior research has largely neglected the impact of Personal Norms alongside constructs such as Green Purchase Attitude (GPA) and Perceived Behavioral Control (PBC). Utilizing established frameworks, including the Norm Activation Model and the Theory of Planned Behavior, this narrative review synthesizes existing literature to bridge this gap. The analysis critically investigates how GPA, PBC, Personal Norms, and GPI interact to shape green purchasing behaviors among Zillennial consumers. The review underscores the essential role of personal normative factors in transforming purchase intentions into tangible actions, thereby enriching current theoretical models. These insights not only advance academic understanding but also provide guidance for marketers and policymakers aiming to enhance consumer perceptions, attitudes, and control, ultimately fostering greater adoption of eco-friendly skincare products.